1991
DOI: 10.1113/expphysiol.1991.sp003473
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin gene‐related peptide inhibits exocrine secretion from the rat pancreas by a neurally mediated mechanism

Abstract: SUMMARYThe mechanism by which calcitonin gene-related peptide (CGRP) inhibits exocrine secretion from the rat pancreas was examined in the isolated, vascularly perfused pancreas and in vitro using freshly isolated pancreatic acini. CGRP (10-10-10-7 M) inhibited the volume and protein output from the perfused pancreas, stimulated by a mixture of the cholecystokinin octapeptide CCK8 (10-10 M) and secretin (10-8 M). The inhibition by CGRP was dose related and maximal at 10-8 M (P < 0-05). CGRP (10-8 M) failed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…The likely mechanism of action involved somatostatin and also sympathetic noradrenergic efferent nerves via ␣-adrenergic receptors (122). Another study using perfused rat pancreas and isolated pancreatic acinar cells confirmed that CGRP inhibited stimulated secretion in vivo, but not in vitro (26). The effect of CGRP was probably indirect, possibly involving cholinergic muscarinic transmission.…”
Section: Pancreatic Hormones and Neuropeptidesmentioning
confidence: 84%
“…The likely mechanism of action involved somatostatin and also sympathetic noradrenergic efferent nerves via ␣-adrenergic receptors (122). Another study using perfused rat pancreas and isolated pancreatic acinar cells confirmed that CGRP inhibited stimulated secretion in vivo, but not in vitro (26). The effect of CGRP was probably indirect, possibly involving cholinergic muscarinic transmission.…”
Section: Pancreatic Hormones and Neuropeptidesmentioning
confidence: 84%
“…Subpopulation of somatostatin cells (Fujimura et al 1988;Sternini et al 1992) CRLR not detected (Martinez et al 2000) ↓ HCO 3 Ϫ secretion a (Helton et al 1989;Bunnett et al 1991;Debas et al 1992 (Böttcher et al 1989) Yes (Jackerott and Larsson 1997)…”
Section: Other Islet Metabolites As Candidates To Influencementioning
confidence: 99%
“…The effects of CCK (10 Ϫ10 M) and secretin (10 Ϫ8 M), both alone and in combination, on pancreatic amylase and flow of pancreatic juice were exam-ined. The doses were selected based on prior experiments to achieve peak (two-to fourfold increase) stimulation of exocrine pancreatic secretion in this model (6). CCK was dissolved in 0.25% BSA-0.1% acetic acid, and secretin was dissolved in 0.1% BSA-normal saline.…”
Section: Methodsmentioning
confidence: 99%
“…CCK was dissolved in 0.25% BSA-0.1% acetic acid, and secretin was dissolved in 0.1% BSA-normal saline. For experiments with SP, neurokinin receptor antagonists, atropine, and TTX, the combination of CCK (10 Ϫ10 M) ϩ secretin (10 Ϫ8 M) was used to induce maximal pancreatic exocrine secretion (6). Unless otherwise specified, all drugs were reconstituted in 1 ml of a 0.1% BSA-normal saline solution before infusion via a sidearm of the aortic cannula.…”
Section: Methodsmentioning
confidence: 99%